Association between Islamic Work Ethics and Employee Commitment Among Medical Staff in the Public Health Sector in Bahrain - Ali Ahmed Ateeq Ali; Mohammed Alzoraiki; Ali Nasser AL-Tahitah; Qais Almaamari; Mokhtar Al-shaibah (International Journal of Intellectual Human Resource Management (IJIHRM), 2024)
Non-Indexed Publication